(untitled) (Journal of Hama University, 2026)
This research aimed to determine the role of the Blue Ocean Strategy in enhancing the sustainable competitive advantage of Tarwada Transport and shipping Company as a case study. For this purpose, the researcher relied on the descriptive analytical approach as a general approach to research, where a questionnaire designed and distributed to a sample of employees at the level of senior and middle management in the company studied, since most of the study variables related to the company’s vision and strategy. The researcher used the statistical program SPSS, version 25, to conduct the statistical description. The research found that there is a statistically significant relationship between the dimensions of the Blue Ocean Strategy represented by (exclusion, increase, reduction, innovation) and enhancing sustainable competitive advantage of Tarwada Transport and shipping Company. The researcher provided an explanation for these results. The research also recommended a set of recommendations, the most prominent of which is that the company under study prepare periodic meetings concerned with sustainable competitive advantage and introduce the Blue Ocean Strategy and its effective role in this advantage, in addition to constantly reviewing the latest developments in the Blue Ocean Strategy.